2016
DOI: 10.1128/aem.00559-16
|View full text |Cite
|
Sign up to set email alerts
|

Population- and Individual-Level Dynamics of the Intestinal Microbiota of a Small Primate

Abstract: Longitudinal sampling for intestinal microbiota in wild animals is difficult, leading to a lack of information on bacterial dynamics occurring in nature. We studied how the composition of microbiota communities changed temporally in free-ranging small primates, rufous mouse lemurs (Microcebus rufus). We marked and recaptured mouse lemurs during their mating season in Ranomafana National Park in southeastern mountainous rainforests of Madagascar for 2 years and determined the fecal microbiota compositions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 51 publications
5
45
0
Order By: Relevance
“…Host-microbiota interactions are, thus, an important factor in vertebrate ecology and evolution (Amato, 2016). However, in contrast to numerous studies on humans and laboratory animals, few studies have investigated the causes and consequences of microbiota variation in wild vertebrates, and studies based on repeated sampling of individually recognizable animals are especially rare (but see Aivelo, Laakkonen, & Jernvall, 2016;Amato et al, 2014Amato et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Host-microbiota interactions are, thus, an important factor in vertebrate ecology and evolution (Amato, 2016). However, in contrast to numerous studies on humans and laboratory animals, few studies have investigated the causes and consequences of microbiota variation in wild vertebrates, and studies based on repeated sampling of individually recognizable animals are especially rare (but see Aivelo, Laakkonen, & Jernvall, 2016;Amato et al, 2014Amato et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that there is pervasive within-individual variation in mouse lemur microbiota (Aivelo et al 2016). Thus, it is understandable why we did not identify statistically significant host variables in microbiota variation (Appendix 4 Table A2).…”
Section: Discussionmentioning
confidence: 99%
“…The national park consist of lowland to montane rainforest between 500 and 1500 meters of elevation. We collected samples and data for nematodes, cestodes, eimeriids and ectoparasites from September to December 2011 and 2012 and microbiota from September to December 2012 along previously described protocol (Aivelo et al 2015; Aivelo, Laakkonen & Jernvall 2016) Shortly, we trapped mouse lemurs nightly on two transects, the first within the park boundaries in secondary forest and the second in peripheral zone in highly degraded campsite area. We measured mouse lemurs, collected samples and tagged previously unseen mouse lemurs for later identification with microchips.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA metabarcoding of fecal samples (i.e., molecular scatology) has been employed to understand several types of data in mammalian taxa, including the genotype of the individual (De Barba et al, 2017), its diet (De Barba et al, 2014;Quemere et al, 2013;Shehzad et al, 2012;Soininen et al, 2013;Zeale, Butlin, Barker, Lees, & Jones, 2011), and its pathogens/parasites (Aivelo, Laakkonen, & Jernvall, 2016;Aivelo, Medlar, Löytynoja, Laakkonen, & Jernvall, 2015;Springer et al, 2017). While most previous studies generally investigated only a single attribute of a population, combining assays for multiple classes of data for a species in a metabarcoding study (i.e., multifaceted DNA metabarcoding; MDM) would likely be an efficient approach to gain an in-depth picture of the diverse ecological interactions of a target species.…”
Section: Introductionmentioning
confidence: 99%